Factores estresantes y su incidencia en el desempeño laboral de un trabajador de 30 años de la Unidad de Policía Comunitaria de la Parroquia Pimocha - Moran Carpio, Victoria Anahis (2023)
Stress has become a term that has been normalized within society, which is why it represents a problem that does not distinguish between age or population group. If stress is not treated in time, it can lead to more serious diseases. On the other hand, job performance is the result of the execution of actions carried out by the worker within his or her work environment. The present case study is carried out based on the stressors and their impact on the work performance of a 30-year-old worker from the Community Police Unit of the Pimocha parish. This case study has a mixed approach; that is, quantitative and qualitative, the types of applied research are descriptive and field. The method applied is the inductive one, which made it possible to apply a detailed analysis of the situations determined in relation to the variables under study. The techniques applied were four: semi-structured interview, clinical observation, clinical history, Job performance evaluation test and Cohen's Perceived Stress Scale. The results of the research allowed us to determine how to presumptively diagnose Acute Stress Disorder 308.3 (F43.0)